Prevalence of stress and its associated factors among students of Al-Maarefa Colleges of Riyadh, Saudi Arabia: A comparative cross-sectional study - Asdaq, Basheeruddin (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objectives: It is an unequivocal fact that the stress is a threat to the physical, emotional, and mental health of an individual. University students are exposed to enormous threat due to ever increasing load of the studies that might not match with their academic outcomes. The present study was designed to achieve a knowledge on the prevalence of stress and its associated factors among students of Al-Maarefa Colleges, Riyadh, Saudi Arabia. Materials and Methods: A self-administered, validated, pretested, and structured questionnaire was completed by 402 students of the College of Medicine, College of Pharmacy, and College of Applied Sciences from Al-Maarefa Colleges of Science and Technology, Riyadh, Saudi Arabia. The questionnaire consisted of demographic data, Perceived Stress Scale, stressors, and stress relievers in addition to soliciting their opinions on the need for stress management education in the curriculum. The collected data were analyzed using analysis of variance and post hoc tests (Fisher’s least significant difference test). The level of statistical significance was defined as P ≤ 0.05. Results: Most of the respondents (66%) of the current study were in the age group of 18–22 years, mainly 80% from the female section with balanced distribution of participants from the College of Medicine (39%) and College of Pharmacy (43%), but the College of Applied Sciences (17%) participants were almost half of the other colleges. This sample size corresponds with the population size of the university where study was carried out. As per our findings, the stress level was significantly high among the College of Medicine students when compared to the College of Applied Sciences. Further, students from both College of Pharmacy and College of Medicine expressed stress of higher magnitude in the Perceived Stress Scale. Academic stressors contributed immensely for inducing stress among most of the students. Conclusion: Students from all three fields of education were exposed to stress; however, it seems that the applied science college students carry low level of stress compared to medical and pharmacy students. Academic factors are the most important stressors; hence the need for specific and targeted measures is necessary to decrease substantially the burden of stress on the students. Teaching techniques and college environments should be adapted to the needs of the students. Finally, regular study habits and adequate preparation can help students to avoid stress.